Problem-Based Teaching Material Innovation: Improving Vocational School Students' Learning Outcomes in Element Symbols and Reaction Equations - Matondang, Silvia Elastari; Nst, Putri Junita Sari (LAVOISIER: Chemistry Education Journal, 2025)
This study aims to determine the improvement in student learning outcomes by applying innovative teaching materials based on Problem-Based Learning, and to analyse the relationship between student characteristics and chemistry learning outcomes using teaching materials based on Problem-Based Learning. The study was conducted on 72 Grade X vocational high school students using an experimental method with a control class and an experimental class. The results showed a significant improvement in learning outcomes in the experimental class (73%) compared to the control class (69%). There was a significant relationship between characteristics such as curiosity, independence, discipline, hard work, and honesty with improved chemistry learning outcomes on the topics of element symbols and chemical equations.